COVID-19 prevention, control and management during dental care in a school clinic - Lira, Ana de Lourdes Sá; Campos, Sávio Henrique Lira; Campos, André Vinícius Lira; Carvalho, Breno Wesley Leal; Paulo, Levy Castelo Branco de (Revista da ABENO, 2022)
This study investigated the effectiveness of physical and mechanical barriers in the prevention, control and management of COVID-19 during dental care. In this cross-sectional study, two research students from the eighth period of the dentistry course performed 24 consultations from January to June 2022, in the 4 specialties under study: surgery (S), restorative dentistry (D), endodontics (E) and periodontics (P). For each specialty researched, there were 3 groups: control (CG), which adopted the current biosafety norms of the Federal Council of Dentistry (FCD); with circular shield (G1) and with rectangular shield (G2). For each specialty, the researcher performed 6 dental appointments, whose patients were chosen by lot to which group they would participate, so that the distribution was equitable between the groups. Aerosol stains were found around office equipment, as well as on professionals’ personal protective equipment (PPE) and close to the patient. The maximum distance found from aerosol splashes to the naked eye was 1.43m during prophylaxis procedures in the CG. In all groups, most of the splashes were found on the PPE used by professionals, especially on gloves, in the professionals’ wrist region; on the patient, on the apron and neck. There was no statistically significant difference between the groups within the specialties (p-value > 0.05), disregarding the comparison between pairs. It was concluded that there was dissemination of aerosol droplets in all dental visits in the 4 specialties studied. Although the PPE proposed by the FCD are effective as a physical barrier to reduce cross-infection and the spread of droplets and aerosols, as well as a preventive measure against COVID-19 during dental care, the professional can use other devices that demonstrate effectiveness, such as the circular screens and the acrylic box, during the dental procedures.